Learning materials template for visual learners / Zuraida Khairudin … [et al.] - Khairudin, Zuraida; Abd Rahman, Hezlin Aryani; Moksin, Mudiana; Hamidi, Saidatul Rahah; Shaffiei, Zatul Amilah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
University institutions are engaged in a sustained and continuous process of producing quality student. Thus it is important for university institutions to focus on improving the teaching and learning method. One important area that has to be emphasized is the student learning styles. Several studies have shown that academic performance of tertiary educational level student is related to their learning styles. The objective of this study is to create the template of learning material for visual learners using Microsoft software. The learning material template will give a clear view of learning techniques among the student. This is pivotal factor for student to attain success in their education. Consequently, lecturers will be able to imporove their teaching method.